Strategic Project «Creative City – Territory of Development» as a Model of Interaction between Flagship University and Region - Tatyana V. Ashutova; Zoia Yu. Zhelnina (Высшее образование в России)
The article presents the experience of Murmansk Arctic State University in the implementation of a unique project for the region – «Creative city – territory of development», which reflects innovative social practices, technologies of project training and the strategy of the University to fulfill its potential in the creative industries. Creative industries are a growth point for the regional “smart specialization”, significantly affecting the quality of life of the local communities and fulfilling not only current, but also emerging human needs. Therefore it is important to involve the younger generation in creative activities in order to develop experience of participation in new socio-economic processes. The discussion about the productivity of classical and project solutions in professional training programs determined the advantage of creative projects of students to present their competencies not only to potential employers, but also to other stakeholders in the development of the region. Initiatives in the Northern Design Cluster and the Tourism and Recreation Cluster of the Murmansk Region have become a new type of university activities; their the projects allow to attract experts to discuss areas of work and clusters cooperation models. Creative industries meet the challenges of the era, when for success the territories must use the resources of cultural brands, shape the quality of life by developing social spaces, non-standard use of color and light in design for psycho-emotional well-being. The project “Creative City – Territory of Development” makes it possible to get feedback from the local communities. The university consistently implements a strategy of expanding areas of participation in the life of the region, conducts research on integrating the modern Arctic design, socio-cultural and economic practices of municipalities. Therefore, the article analyzes the growth factors and ways of influence of the university on the regional community in the field of creative industries; emphasizes the complexity of the tasks and the increase in the number of stakeholders in the creative industries, underlines the fact that university projects are both the creative products and creative technologies for the formation of professional competences in the welfare industry, tourism and design.